Unprecedented North American snowstorm and East Asian cold wave in January 2016: Critical role of the Arctic atmospheric circulation. (22nd October 2021) - Si, Dong; Jiang, Dabang; Lang, Xianmei; Fu, Shenming
Abstract: During January 21–24, 2016, most land areas in the Northern Hemisphere experienced extreme low temperatures. In North America, a historic snowstorm hit the northern and eastern United States. In East Asia, an unprecedented cold wave occurred and led to record‐breaking low temperatures in many regions. In this study, observational analyses revealed that both extreme events were triggered by a remarkable change in atmospheric circulation in the Arctic region in early January 2016, which switched from a concentric ring pattern to a dipole pattern. The dipole pattern resulted in two inverted Ω‐shaped circulation patterns that dominated the North America and East Asia. The inverted Ω‐shaped circulation patterns induced remarkable tropopause folding, which conveyed high‐potential‐vorticity cold air downwards from the lower stratosphere of Arctic to the middle and lower troposphere of North America, which increased cyclonic vorticity and negative height perturbations, and converged with moist air from the western North Atlantic and Gulf Stream, resulting in a severe snowstorm in the northern and eastern United States from 22 to 24 January. In East Asia, the tropopause folding transported high‐potential‐vorticity cold air downwards to the middle and lower troposphere of East Asia, resulting in the outbreak of a severe cold wave in East Asia from 21 to 24 January. Abstract : During January 21–24, 2016, most land areas in the Northern Hemisphere experienced unprecedented low temperatures. In North America, a historic snowstorm hit the northern and eastern United States. In East Asia, a severe cold wave occurred and led to record low temperatures in many regions. Observational analyses revealed that both extreme events were triggered by a remarkable change in atmospheric circulation in the Arctic region in early January 2016.